Theorising from the Belt and Road Initiative (一带一路). (26th October 2021) - Lin, Shaun; Shimazu, Naoko; Sidaway, James D.
Abstract : As frame for the set that follows, this article first considers the range of theoretical interpretations of China's Belt and Road Initiative (BRI). Our focus, however, is on a related yet distinct set of questions. Rather than theorising BRI per se, we approach BRI as a source of theoretical implications and reflection – asking what it signals and implies for wider cultural, economic, political, social and urban theories, and for histories of and afterlives of imperial geopolitics.